Interdisciplinary and Collaborative Approaches Needed to Determine Impact of COVID-19 on Older Adults and Aging: CAG/ACG and CJA/RCV Joint Statement. Issue 3 (10th September 2020) - Meisner, Brad A.; Boscart, Veronique; Gaudreau, Pierrette; Stolee, Paul; Ebert, Patricia; Heyer, Michelle; Kadowaki, Laura; Kelly, Christine; Levasseur, Mélanie; Massie, Ariane S.; Menec, Verena; Middleton, Laura; et al.
ABSTRACT: The COVID-19 pandemic and subsequent state of public emergency have significantly affected older adults in Canada and worldwide. It is imperative that the gerontological response be efficient and effective. In this statement, the board members of the Canadian Association on Gerontology/L'Association canadienne de gérontologie (CAG/ACG) and the Canadian Journal on Aging / La revue canadienne du vieillissement ( CJA / RCV ) acknowledge the contributions of CAG/ACG members and CJA / RCV readers. We also profile the complex ways that COVID-19 is affecting older adults, from individual to population levels, and advocate for the adoption of multidisciplinary collaborative teams to bring together different perspectives, areas of expertise, and methods of evaluation in the COVID-19 response.